BACTERIA LOADS OF PUBLIC TRANSPORT IN THE TAMALE METROPOLIS, GHANA - Abdulai, M.; Abubabakari, Z. I.; Cobinna, S. J.; Oduro, D. (UDS International Journal of Development, 2021)
Investigations for pathogenic microbes on surfaces of objects have been attaining significant consideration from public health researchers for some time now. This is especially because of the risk of the spread of diseases of public health concern. Consequently, this study was conducted to provide information on bacterial contamination levels in taxis and motorised tricycles operating from the Tamale Main Taxi Rank. Forty samples from taxis and tricycle seats were collected and analysed. All samples contained Escherichia coli, Salmonella spp, and Shigella spp. Taxis contained significantly (p < 0.006) more bacteria than tricycles (mean bacterial loads of 20.35×106 CFU/ml and 2.80×10 6 CFU/ml respectively). Also, considering the materials with which the vehicle seats were made vinyl contained more bacteria (14.06×106 CFU/ml) than cloth (10.98×106 CFU/ml) and polythene (1.12×106 CFU/ml). Using the Kruskal-Wallis test for analysing bacteria loads across material types, it was found that there was a significant difference (p < 0.026) between bacteria numbers and material types. The bacteria isolates showed resistance to the antibiotics, ampicillin (10 μg), Ceftazidime (30 μg), Cefotaxime (30 μg), and Ciprofloxacin (5 μg). Taxis and tricycles in some parts of the Metropolis operate under poor hygienic conditions. It is recommended that routine cleaning and disinfection of vehicles as well as the practice of personal hygiene be highly encouraged to keep a safer and healthier urban population and environment. Keywords: Escherichia coli, Pathogenic, Salmonella spp, Shigella spp